Japanese versions of the Executive Interview (J-EXIT25) and the Executive Clock Drawing Task (J-CLOX) for older people. (August 2014) - Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Uchida, Hiroyuki; Nakaaki, Shutaro; Koumi, Hiroyuki; Mimura, Masaru; et al.
ABSTRACT Background: The aim of the study was to develop the Japanese versions of Executive Interview (J-EXIT25) and Executive Clock Drawing Task (J-CLOX) and to evaluate the aspects of executive function that these two tests will be examining. Methods: The concurrent validity and reliability of J-EXIT25 and J-CLOX were first examined in all participants (n = 201). Next, the relationship between the two tests was examined using receiver operating characteristic (ROC), correlation, and regression analyses in healthy participants (n = 45) and participants with mild cognitive impairment (n = 36) and dementia (n = 95). Results: Satisfactory concurrent validity and reliability of J-EXIT25 and J-CLOX were shown. ROC analysis indicated that J-EXIT25 and J-CLOX1 were superior to the Frontal Assessment Battery, but inferior to the Mini-Mental State Examination (MMSE), in discriminating between non-dementia and dementia. J-EXIT25, J-CLOX1, and J-CLOX2 scores were significantly correlated with age, scores on the MMSE, Instrumental Activities of Daily Living (IADL) and Physical Self-Maintenance Scale (PSMS), and care level. In stepwise regression analyses of IADL scores, MMSE and J-EXIT25 were significantly independent predictors in men, and MMSE, age, and J-CLOX1 were significantly independent predictors in women. J-EXIT25, MMSE, and J-CLOX1 were significantly independent predictors in stepwise regression analysis of PSMS scores, and J-EXIT25 was the only significantly independent predictor in stepwise regression analysis of care level. Conclusions: J-EXIT25 and J-CLOX are valid and reliable instruments for assessment of executive function in older people. The present results suggest that these tests have common and distinct psychometric properties in the assessment of executive function.